2019
DOI: 10.12681/jhvms.19616
|View full text |Cite
|
Sign up to set email alerts
|

First report of Angiostrongylus vasorum in red foxes (Vulpes vulpes) in Serbia

Abstract: Angiostrongylosis caused by Angiostrongylus vasorum is an emerging disease in Europe and the red fox (Vulpes vulpes) is considered as a main reservoir species for this parasite. Since there have been no reports of A. vasorum in red foxes in Serbia at the time of carrying out our investigations, the aim of the investigations was to explore the role of red foxes in South Banat (northern Serbia) as reservoirs for A. vasorum. Legally hunted foxes were autopsied in the Veterinary Specialised Institute “Pančevo”. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(44 reference statements)
0
1
0
Order By: Relevance
“…During this period, a significant change in the biodiversity of fox parasitofauna was established. Parasitic species such as Diphyllobothrium latum, Mesocestoides litteratus, Spirocerca lupi, Echinococcus multilocularis and Angiostrongylus vasorum (Gavrilović et al, 2018;Lalošević et al, 2018;Pavlović et al, 2008Pavlović et al, , 2004Pavlović et al, , 2001), which were not previously present in the Western Balkans, were identified.…”
Section: O N L I N E F I R S T Resultsmentioning
confidence: 95%
“…During this period, a significant change in the biodiversity of fox parasitofauna was established. Parasitic species such as Diphyllobothrium latum, Mesocestoides litteratus, Spirocerca lupi, Echinococcus multilocularis and Angiostrongylus vasorum (Gavrilović et al, 2018;Lalošević et al, 2018;Pavlović et al, 2008Pavlović et al, , 2004Pavlović et al, , 2001), which were not previously present in the Western Balkans, were identified.…”
Section: O N L I N E F I R S T Resultsmentioning
confidence: 95%